On the compound binomial risk model with delayed claims and randomized dividends - Kam Pui Wat; Kam Chuen Yuen; Wai Keung Li; Xueyuan Wu (Risks, 2018)
This paper extends the work of Yuen et al. (2013), who obtained explicit results for the discount-free Gerber-Shiu function for a compound binomial risk model in the presence of delayed claims and a randomized dividend strategy with a zero threshold level. Specifically, we establish a recursion method for computing the Gerber-Shiu expected discounted penalty function, which entails a number of important quantities in ruin theory, within the framework of the compound binomial aggregate claims with delayed by-claims and randomized dividends payable at a non-negative threshold level.
Keywords: 330; compound binomial riskmodel; delayed claims; Gerber-Shiu function; randomized dividends